The Construction of Literacy Competence of Junior High School Students in Semarang Based on PISA Standards - Nurfadilah, Kurnia Dewi; Zulaeha, Ida (Pascasarjana Universitas Negeri Semarang, 2018)
The objective of this study was to analyze the construction of literacy competence of junior high school students based on PISA standards. The construction of literacy competence in junior high school students could be viewed from reading competence and writing competence. This study used quantitative descriptive method with quantitative and qualitative data analysis techniques. The results showed that 96% students were able to find and get information in the text, 88.3% were able to understand and interpret the text, 66.7% students were able to identify the text, 35% were able to reflect the contents of the text, and 37.5% were able to evaluate the text, while for writing competence 78% students were able to write well according to the organization, language use, and function of the text. The analysis results of the construction of literacy competence could be used as references to improve the literacy competence of junior high school students.